The dust bowl [videorecording (DVD)] - Coyote, Peter; Burns, Ken, 1953-; Burns, Ken, 1953- (PBS, 2012)
Ken Burns documents the worst human-made ecological disaster in American history, when a frenzied wheat boom on the southern Plains, followed by a decade-long drought during the 1930s, nearly swept away the breadbasket of the nation. Vivid interviews, dramatic photographs, and seldom-seen movie footage bring to life incredible stories of human suffering and perseverance. Includes bonus features.